Room cleaning robot movement using A* algorithm and imperfect maze - Vera Suryani; Kinkin Agustriana; Andrian Rakhmatsyah; Rizka Reza Pahlevi (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2023)
Cleanliness is a mandatory requirement to help prevent virus spread. The cleaning process can be done automatically by humans or robotic devices. If a robot does this process, it is a must that the robot is able to explore the room autonomously. The robot movement in room tracking should reach all points without obstructions and return to its initial position. This study simulated the movement of a room explorer robot using the imperfect maze method, as well as searching a room that has not been explored using the A* algorithm. The A* algorithm was also used to find the shortest path to reach the initial place of the robot when the room exploration was completed. The results of the simulation showed that the imperfect maze could be used to explore the room well, and A* algorithm is quite optimal to be used for searching both the unexplored room and the path to return to its initial position